Western Union Telegram from Robert J. Downey - Robert J. Downey:::::: (1968)
This Western Union telegram invites Jane Tolmach to attend a visit by Vice President Hubert H. Humphrey to the TRW Systems Group in Redondo Beach on Tuesday, September 10 at noon. Humphrey is scheduled to address 14,000 employees, invited guests, and the public under the company's Good Government Program. The message provides arrival instructions and RSVP details and is signed by Robert J. Downey, Director of Administrative Operations at TRW Systems Group.